Peningkatan Ketahanan Baja SS-304 terhadap Korosi Menggunakan Lapisan Tembaga dan Inhibitor dari Tanin Ekstrak Daun Sirsak dengan Metode Elektrodeposisi - Letmi Syara; Dahyunir Dahlan (Jurnal Fisika Unand, 2026)
Research has been conducted on improving the corrosion resistance of SS-304 stainless steel using copper coating and an inhibitor derived from soursop leaf extract via the electrodeposition method. The main objective of the research was to determine the optimal concentration of soursop leaf extract as an inhibitor for protecting the steel from the corrosion. The inhibitor concentrations used were 0%; 1%; 2%; 3%; 4% and 5%. Layer characterization was performed using an optical microscope to observe the surface of the electrodeposited coating, while X-ray diffraction (XRD) was used to identify the phase and crystal structure of the formed protective layer. The corrosion rate was calculated based on mass change after immersion in a corrosive medium. The result showed that the most optimal corrosion inhibition was achieved at an inhibitor concentration of 4%, with an inhibition efficiency of 94%. At this concentration, the lowest corrosion rate was recorded, and the surface morphology appeared the smoothest compared to the other prepared samples. Crystal phase analysis revealed that before immersion, the protective layer consisted of the copper (Cu) phase, whereas after immersion, a new phase was formed, namely copper oxide (CuO).